2022
DOI: 10.1080/13621718.2021.2010449
|View full text |Cite
|
Sign up to set email alerts
|

Laser pressure welding of dissimilar aluminium and copper: microstructure and mechanical property

Abstract: In this work, laser pressure welding of dissimilar aluminium and copper was conducted at a high welding speed of 15 m min −1 . One-micron intermetallic compounds (IMCs) layer with heterogeneous dual-phases (copper and γ -Al 4 Cu 9 phases) laminates in the joint interface were observed by transmission electron microscopy. The results showed that the combination of two joining mechanisms led to improved mechanical property, namely the mechanical interlocking due to the curved interface and the metallurgical bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…When analyzing publications, it was found that after laser welding, most researchers conduct mechanical tests (mainly tensile or shear strength tests) [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ] while vital Al/Cu joints properties are thermal conductivity and electrical conductivity [ 78 ]. That is, the main area of application is the branch of electrical contact or heat transfer products and devices.…”
Section: Laser Welding Of Aluminum Alloys To Coppermentioning
confidence: 99%
See 2 more Smart Citations
“…When analyzing publications, it was found that after laser welding, most researchers conduct mechanical tests (mainly tensile or shear strength tests) [ 71 , 72 , 73 , 74 , 75 , 76 , 77 ] while vital Al/Cu joints properties are thermal conductivity and electrical conductivity [ 78 ]. That is, the main area of application is the branch of electrical contact or heat transfer products and devices.…”
Section: Laser Welding Of Aluminum Alloys To Coppermentioning
confidence: 99%
“…A significant advantage of laser welding, which allows reducing the thickness of the IMC, is the use of high-speed laser welding up to 95–155 mm/s [ 75 ], 250 mm/s [ 71 ], 80–800 mm/s [ 76 ], which makes it possible to obtain a minimum IMC with a thickness of 1–4 μm with heterogeneous dual-phases (copper and γ-Al 4 Cu 9 phases), which is also formed at solid-state welding [ 82 ]. The recently published work [ 71 ] on laser pressure welding is of particular interest, a process that combines laser welding with rolling welding, with a laser beam directed between two converging sheets of aluminum and copper. The authors of this work were the first to use this technique for welding the pure aluminum, then for pure copper, which are known to reflect laser irradiation strongly, and then for their combination.…”
Section: Laser Welding Of Aluminum Alloys To Coppermentioning
confidence: 99%
See 1 more Smart Citation